Wpływ nowego programu nauczania matematyki w szkołach średnich na wyniki nauczania matematyki na uczelniach ekonomicznych - Miśkiewicz, Monika (The impact of new mathematics curriculum in secondary schools on learning outcomes of mathematics at the universities of economic, 2011)
The author of this paper conducted research on the impact of the new curriculum of mathematics in secondary schools on the results achieved by students of the University of Economics in Katowice. She used marks in mathematics and mathematical analysis achieved by her students in the years 20012010. Moreover she conducted a survey about the level of difficulty of the tasks-leaving and the level of difficulty of the tasks, which students solved in class. She presented the test results that reached her students in mathematical analysis in 2010, too
Didactics of Mathematics, 2011, Nr 8 (12), s. 101-112
Keywords: mathematics curriculum in secondary school; standards for the school-leaving exam; results achieved by students